2021
DOI: 10.15847/obsobs15120211696
|View full text |Cite
|
Sign up to set email alerts
|

University students engagement with fake news: the portuguese case

Abstract: The development of technological and communication platforms generates academic, political and social debates. In the field of Media Studies, there is a special concern with the younger generations, as studies document that they express particular behaviors due to the increased diffusion of digital consumption in their lives (Silveira & Amaral, 2018). In the field of media literacy, news literacy becomes even more relevant today due to the rise of fake news, which is one of the biggest challenges for digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…A study on Covid-19-related knowledge among Jordanian university students found similarly the preponderance of internet, especially of social media, as source of information (Olaimat et al, 2020). Some university students in a Portuguese study depend exclusively on social media for Covid-19-related information (Silveira & Gancho, 2021). Another study among Portuguese university students found that searches on social media or using internet search engines rather than a direct consultation of public body websites was associated with insufficient digital health literacy (Rosário et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A study on Covid-19-related knowledge among Jordanian university students found similarly the preponderance of internet, especially of social media, as source of information (Olaimat et al, 2020). Some university students in a Portuguese study depend exclusively on social media for Covid-19-related information (Silveira & Gancho, 2021). Another study among Portuguese university students found that searches on social media or using internet search engines rather than a direct consultation of public body websites was associated with insufficient digital health literacy (Rosário et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Este estudo é um contributo para o debate contemporâneo no campo da comunicação e da literacia mediática no contexto das fake news. Apesar de o fenómeno das fake news carecer ainda de mais investigação em Portugal, encontramos vários estudos na literatura que procuraram perceber os hábitos e a suscetibilidade dos jovens portugueses em relação a estas (Catalina-García et al, 2019;Figueira & Santos, 2019;Silveira & Gancho, 2021;Sobral & de Morais, 2020). No entanto, não só em Portugal, mas também noutros países, o interesse académico tem-se focado em estudantes universitários (de Vicente Domínguez et al, 2021;Herrera & Belda, 2021;Leeder, 2019).…”
Section: Introductionunclassified
“…Quanto aos hábitos dos mais jovens de consumir notícias, sabe-se que acedem preferencialmente a notícias online, através maioritariamente de smartphones (Ahmed, 2020;Amaral et al, 2017;Antunovic et al, 2018;Johnson & St. John III, 2020;Silveira & Gancho, 2021), ainda que a exposição a notícias aconteça de forma acidental e não-direta (Antunovic et al, 2018).…”
Section: Introductionunclassified